Changes in lean and skeletal muscle body mass in adult females with anorexia nervosa before and after weight restoration. Issue 1 (February 2017) - El Ghoch, Marwan; Pourhassan, Maryam; Milanese, Chiara; Müller, Manfred J.; Calugi, Simona; Bazzani, Paola Vittoria; Dalle Grave, Riccardo
Summary: Background & aims: Data on the deficits in lean body mass (LBM) and total body skeletal muscle mass (SM) in anorexia nervosa (AN) is scarce and inconsistent. Furthermore, the usefulness of the reported body mass index (BMI) severity cut-off for AN has not been tested with respect to these important parameters. The study had two aims, namely to study LBM patterns and SM in adult females with AN before and after weight restoration, and to examine the clinical usefulness of the 16.5 kg/m 2 BMI cut-off for assessing the protein status in terms of LBM and SM in AN patients. Methods: Body composition was measured by dual-energy X-ray absorptiometry (DXA) before and after weight gain in 90 adult female inpatients with AN, and 90 controls matched by post-treatment BMI and age. Patients were stratified into two groups using BMI 16.5 kg/m 2 as a cut-off. Results: Before weight restoration, patients in the BMI ≤ 16.5 kg/m 2 subgroup (n = 65) had lower LBM, SM and lean extremity mass percentage, but higher %LBM and lean trunk-to-extremity ratio on average than controls. However, those with BMI >16.5 kg/m 2 (n = 25) displayed lower lean extremity mass percentage and higher %LBM, but no significant differences in LBM and SM with respect to controls. Moreover the time × subgroup interaction was significant in terms of LBM and SM, meaning that, changes occur in different manner over time in the two AN subgroups. However no differences were found between the two AN subgroups in either demographic or other eating disorder characteristics. After weight gain, normalization of LBM, %LBM, lean extremity mass percentage and SM was achieved across the entire AN sample, and the BMI ≤ 16.5 kg/m 2 subgroup. The fat mass was the major determinant of gain in LBM; the higher the FM at baseline, the greater the increase in LBM. Conclusions: Our results suggest a BMI cut-off ≤16.5 kg/m 2 as a clinical threshold for determining AN severity. As short-term weight restoration is associated with a normalization in LBM and SM, it appears that biological regulation of weight gain remains intact in AN, i.e., unaffected by the severity of malnutrition. Clinical trials registry: Changes in lean and skeletal muscle body mass in adult females with anorexia nervosa before and after weight restoration (ISRCTN168721194).